Acid‐suppression medications and bacterial gastroenteritis: a population‐based cohort study - Wei, Li; Ratnayake, Lasantha; Phillips, Gabby; McGuigan, Chris C.; Morant, Steve V.; Flynn, Robert W.; Mackenzie, Isla S.; MacDonald, Thomas M. (British journal of clinical pharmacology, 2017)
Aims To investigate whether acid‐suppression medicines (ASMs) increase the risk of bacterial gastroenteritis. Methods A population‐based, propensity‐score matched cohort study using a record‐linkage database in Tayside, UK. The study consisted of 188 323 exposed to ASMs (proton‐pump inhibitors and histamine‐2 receptor antagonists) and 376 646 controls (a propensity‐score matched cohort from the rest of population who were not exposed to ASMs) between 1999 and 2013. The main outcome measure was a positive stool test for Clostridium difficile, Campylobacter, Salmonella, Shigella or Escherichia coli O157. The association between ASMs and risk of bacterial gastroenteritis was assessed by a Cox regression model. Results There were 22 705 positive test results (15 273 C. difficile [toxin positive], 6590 Campylobacter, 852 Salmonella, 129 Shigella and 193 E. coli O157, not mutually exclusive) with a total of 5 729 743 person‐years follow up time in Tayside, 1999–2013. The adjusted hazard ratios for culture positive diarrhoea for the proton‐pump inhibitors and histamine‐2 receptor antagonists exposed vs. unexposed cohort were 2.72 (95% confidence interval [CI] 2.33, 3.17) during follow–up time for samples submitted from the community and 1.28 (95% CI 1.08, 1.52) for samples submitted from hospitals. Compared with the unexposed cohort, patients in the exposed group had increased risks of C. difficile and Campylobacter [adjusted hazard ratios of 1.70 (95% CI 1.28, 2.25), 3.71 (95% CI 3.04, 4.53) for community samples, and 1.42 (95% CI 1.17, 1.71), 4.53 (95% CI 1.75, 11.8) for hospital samples, respectively]. Conclusions The results suggest that community prescribed ASMs were associated with increased rates of C. difficile and Campylobacter positive gastroenteritis in both the community and hospital settings.